A Light‐Activated Metal Complex Targets both DNA and RNA in a Fluorescent in Vitro Transcription and Translation Assay. Issue 4 (31st January 2014) - Heidary, David K.; Glazer, Edith C.
Abstract A coupled in vitro transcription and translation (IVTT) assay that uses GFP as a fluorescent reporter allowed the potency of a light‐activated cytotoxic ruthenium agent to be quantified. The compound inhibits the function of both DNA and mRNA only upon light activation. The IVTT functional assay provides estimates of potency that are consistent with cellular cytotoxicity values, in marked contrast to the values obtained from traditional DNA‐damage assays.